2021
DOI: 10.1002/app.50710
|View full text |Cite
|
Sign up to set email alerts
|

Ionic liquids enhanced performance of PVC gels actuator

Abstract: Stimulated devices are highly demanded for actuators and artificial muscles in the recent era but susceptible to low deformation at an applied voltage. In the present work, ionic liquids (ILs) based gel films were prepared from the polyvinyl chloride (PVC), dibutyl adipate (DBA), 1-butyl, 3-methimidazolium chloride, and 1-pentyl-3-methylimidazolium hexafluorophosphate by a simple solvent evaporation method. The structural, morphological, optical, and mechanical properties of the composite PVC/ILs gel were char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 31 publications
2
12
1
Order By: Relevance
“…5 a to have the largest displacement of the three with substantial increased contraction over P4 with the same electrode configuration. P4-IL1 showed improvement over the unmodified gel as well, both results are consistent with previous studies showing better actuation performance for gels with conductive fillers 19 , 21 , 23 .
Figure 5 ( a ) Contraction of a mesh actuator for gels with different additive content.
…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…5 a to have the largest displacement of the three with substantial increased contraction over P4 with the same electrode configuration. P4-IL1 showed improvement over the unmodified gel as well, both results are consistent with previous studies showing better actuation performance for gels with conductive fillers 19 , 21 , 23 .
Figure 5 ( a ) Contraction of a mesh actuator for gels with different additive content.
…”
Section: Resultssupporting
confidence: 92%
“…The ions are able to dissociate and relax at higher frequencies than the ions and injected charges present in the unmodified gels alone. This leads to ILs having slightly larger deformation, but much faster actuation at lower voltages as reported upon previously by multiple other groups 19 – 21 . The electrode polarization time and maximum apparent permittivity are found through the fitting of a Cole–Cole equation to the tan( δ ) spectra of the gels and can be seen in Table 2 .…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…The simple steps of dissolving in organic solvents, adding plasticizers to plasticize, and then drying to remove the volatile organic components result in a soft colloidal structure with mechanical strength varying with the content of plasticizers. , However, a more stable fluorinated PVC material has also been used to improve the thermal stability of the material and has been applied to a PVC gel system to enhance the performance. At the same time, the polarity of halogen atoms also increased its actuation effect. , It was found that elaborating on the relevant deformation principles with Raman tests could provide a clear characterization and interpretation of the response process. , …”
Section: Introductionmentioning
confidence: 99%